Different interaction motifs of dipolar S = O center dot center dot center dot C = O contacts that associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-7,7-dimethyl-2-oxo-bicyclo[2.2.1]heptan-1-ylmethyl]-sulfonyl-myo-inositol 1,3,5-ortho-acetate - Manoj, Kochunnoonny; Gonnade, R. G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C‐Structural Chemistry, 2007)
Diastereomeric mixtures of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoesters associate in their crystal structures via different geometries of S=O...C=O short contacts, depending upon the substitution. A comparison of the dimeric association in the orthoacetate and orthoformate (solvated) derivatives shows a sheared parallel motif of dipolar S=O...C=O contacts bridging the former, whereas perpendicular S=O...C=O contacts occur in the latter. The title compound, C32H34O11S, is chiral, owing to the presence of the camphor moiety.